The household financial burden of non-communicable diseases in low- and middle-income countries: a systematic review - Joseph Kazibwe; Phuong Bich Tran; Kristi Sidney Annerstedt (BMC, 2021)
Abstract Background The chronic nature of noncommunicable diseases (NCD) and costs associated with long-term care can result in catastrophic health expenditure for the patient and their household pushing them deeper into poverty and entrenching inequality in society. As the full financial burden of NCDs is not known, the objective of this study was to explore existing evidence on the financial burden of NCDs in low- and middle-income countries (LMICs), specifically estimating the cost incurred by patients with NCDs and their households to inform the development of strategies to protect such households from catastrophic expenditure. Methods This systematic review followed the PRISMA guidelines, PROSPERO: CRD42019141088. Eligible studies published between 1st January 2000 to 7th May 2020 were systematically searched for in three databases: Medline, Embase and Web of Science. A two-step process, comprising of qualitative synthesis proceeded by quantitative (cost) synthesis, was followed. The mean costs are presented in 2018 USD. Findings 51 articles were included, out of which 41 were selected for the quantitative cost synthesis. Most of the studies were cross-sectional cost-of-illness studies, of which almost half focused on diabetes and/or conducted in South-East Asia. The average total costs per year to a patient/household in LMICs of COPD, CVD, cancers and diabetes were $7386.71, $6055.99, $3303.81, $1017.05, respectively. Conclusion This review highlighted major data and methodological gaps when collecting data on costs of NCDs to households along the cascade of care in LMICs. More empirical data on cost of specific NCDs are needed to identify the diseases and contexts where social protection interventions are needed most. More rigorous and standardised methods of data collection and costing for NCDs should be developed to enable comprehensive and comparable evidence of the economic and financial burden of NCDs to patients and households in LMICs. The available evidence on costs reveals a large financial burden imposed on patients and households in seeking and receiving NCD care and emphasizes the need for adequate and reliable social protection interventions to be implemented alongside Universal Health Coverage.